The Live Broadcast Business Model of Cross-Border E-Commerce - Zhao, Xinran (International Journal of Global Economics and Management, 2024)
With the development of Internet e-commerce, the global economic and business landscape has undergone profound changes. This article will understand the market innovation and expansion and supply chain optimization through the business model of e-commerce live broadcasting. As more and more individuals, enterprises, institutions and even people from all walks of life join the trend of live broadcasting, they try to carry out diversified activities such as product display, promotion, knowledge sharing, talent show and public welfare activities through live broadcasting platforms. With the help of real-time online interactive communication and intuitive and vivid picture presentation, it has attracted and maintained the attention and participation of a large number of users. In this work, with the rapid development of e-commerce industry and the wide application of new technologies such as 5G and VR/AR, live events have evolved from a single information dissemination channel to a diversified form of interaction covering entertainment, shopping, education, business and other fields.